2004
DOI: 10.1080/00288306.2004.9515078
|View full text |Cite
|
Sign up to set email alerts
|

Provenance history of a Late Triassic‐Jurassic Gondwana margin forearc basin, Murihiku Terrane, North Island, New Zealand: Petrographic and geochemical constraints

Abstract: The Murihiku Terrane in the North Island was a forearc basin adjacent to a volcanic arc along the eastern margin of Gondwana during the Mesozoic. The rocks that infill the basin are mainly volcaniclastic sandstones and mudstones, often turbiditic, with sparse shellbeds, rhyolitic tuffs, carbonaceous sandstones, plant beds, concretionary horizons, and rare thick granitoid-rich conglomerates. Petrographic studies of the rock fragments in the sandstones show that andesites are the dominant lithic type, but there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…However, anhydrous 100 wt% normalised analyses match the petrography of an andesitic volcaniclastic sandstone and also lie within the field of early-Middle Jurassic sandstones from the Murihiku Terrane (Fig. 5a) (Briggs et al 2004). …”
Section: Geochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, anhydrous 100 wt% normalised analyses match the petrography of an andesitic volcaniclastic sandstone and also lie within the field of early-Middle Jurassic sandstones from the Murihiku Terrane (Fig. 5a) (Briggs et al 2004). …”
Section: Geochemistrymentioning
confidence: 99%
“…The apparent absence of Wanaea species suggests an age younger than the ohineruru Formation (Heterian) of the kirikiri Group. Briggs et al (2004) showed that the Late Jurassic sandstones of the Huriwai and apotu Groups (Fig. 4) comprise silicarich and silica-poor facies that are different in composition from the early-Middle Jurassic sandstones (Fig.…”
Section: Palynologymentioning
confidence: 99%
“…Petrographic and geochemical studies of Murihiku Terrane samples show that they derived from direct volcanic eruptive materials and mainly from erosion of a volcanic arc terrane (Roser et al 2002;Briggs et al 2004). The sediments and tuff accumulated within a forearc basin probably underlain by oceanic crust (Spörli 1987;Aita and Spörli 1992).…”
Section: Geological Settingmentioning
confidence: 99%
“…This terrane has long been regarded as a Triassic-Jurassic forearc basin based on its simple structure, its well-bedded and fossil-rich character and its volcanic arc provenance (Briggs et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most of this fill is offshore in the subsurface, but an exhumed window of the Neogene succession is exposed onland in eastern Taranaki Peninsula and the king Country region ( vi s e dAJ V, 23J ul y2007) ka mp et al 2004). Basement rocks are Paleozoic and Mesozoic granite and schist west of Taranaki Fault and Triassic-Jurassic sandstone and mudstone, typically greywacke and argillite, east of it (Mortimer 1995;Briggs et al 2004).…”
Section: Geological Settingmentioning
confidence: 99%